Outcomes of single-dose peri-procedural antibiotic prophylaxis for endoscopic ultrasound-guided fine-needle aspiration of pancreatic cystic lesions. Issue 5 (October 2014) - Marinos, Emmanuel; Lee, Sunny; Jones, Brian; Corte, Crispin; Kwok, Avelyn; Leong, Rupert W
Background: Endoscopic ultrasound (EUS)-guided fine-needle aspiration (FNA) is a technique frequently used to diagnose solid and cystic lesions of the pancreas. Antibiotic prophylaxis has been recommended for EUS-FNA of pancreatic cystic lesions but is not universally observed. The most effective antibiotic and the most efficacious route and regimen of administration are also unknown. Objective: This cohort study was undertaken to evaluate whether single-dose piperacillin/tazobactam or ciprofloxacin given at the time of the procedure effectively prevents major adverse events and to audit the adherence to this protocol in the setting of EUS-FNA of pancreatic cystic lesions. Design: Consecutive EUS-FNA procedures of pancreatic cystic lesions were performed at Concord Hospital and significant variables regarding the procedure and adverse events were recorded. Patients were also contacted by telephone to follow-up any subacute adverse events they may have experienced. Patients: Over a 30 month period (January 2010–July 2012), a total of 85 EUS-FNAs of pancreatic cysts were performed on 80 different patients. The mean age was 63.2 years (range 17–89 years; 58% females). Interventions: Single-dose piperacillin/tazobactam IVs was administered to 87% of patients, while 12% of patients received ciprofloxacin IVs. Results: No patients developed cyst infection, fever, or sepsis (0%) and one patient (1.2%) was hospitalised for self-limited nausea without adverse sequelae. Conclusions: Single-dose piperacillin/tazobactam at the time of EUS-FNA of pancreatic cysts is an effective prophylaxis of cyst infection or sepsis and can be conveniently given as a single-dose peri-procedurally without further oral antibiotics.